Metastatic myxoid liposarcoma to the tongue: a unique intraoral metastasis - Tatsis, Dimitris; Deligiannidis, Dimitris; Papaemmanouil, Styliani; Vahtsevanos, Konstantinos (Contemporary Oncology/Współczesna Onkologia, 2020)
The first case of a myxoid liposarcoma metastatic to the tongue of a 78-year-old male patient with primary scrotal liposarcoma for the past seven years is reported. The patient presented with a firm exophytic mass of the left dorsal surface of the tongue, sized 4 to 4.5 cm, with oedema and bleeding. Myxoid liposarcoma is a malignancy with relatively good prognosis and low metastatic rate but high local recurrence. This is the second case report recorded of a metastatic liposarcoma to the oral cavity. Clinical and imaging considerations, as well pathological details concerning the myxoid liposarcoma, are described. Key words: myxoid liposarcoma, tongue, metastasis.